Epidemiological characterization of COVID-19 in children under 18 years old in Mexico: an analysis of the pandemic - Takane-Cabrera, Isamu Daniel; Ortega-Vargas, Fanny Yasmin; Díaz-Torres, Ilen Adriana; Herrera-González, Aldo Agustin; Villa, Antonio R.; García-León, Miguel Leonardo; Bautista-Carbajal, Patricia; Pérez-Sastre, Miguel A.; Cortazar-Maldonado, Luis Alberto; Díaz-Ramírez, Jorge Baruch; Wong-Chew, Rosa Maria (Frontiers in Pediatrics, 2025)
The study aimed to describe the characteristics and risk factors associated with disease severity across six waves of COVID-19 in the pediatric population in Mexico. Methods: A cohort study was conducted using data from the Mexican Ministry of Health, covering the period from March 2020 to March 2023. The dataset included patients under 18 years of age with confirmed SARS-CoV-2 infection. Univariate, bivariate, and logistic regression analyses were performed to determine demographic and clinical characteristics, mortality across waves, and age group distributions. Results: Of the total cohort, 9.5% were children, with 497,428 confirmed cases. Among these, 50% were male, 4.4% required hospitalization, and there were 1,447 (0.03%) deaths. The highest prevalence was observed in the 12 to 17-year age group (52%), followed by the 5 to 11-year age group (32%), with incidence rates peaking towards the end of 2021 and the early 2022. Although the 0-2-year age group represented 9.6% of cases, it had higher hospitalization (40%), ICU admission (58%), and case fatality rate (CFR) (44%). Cardiovascular disease, hypertension, diabetes and immunosuppression were identified as risk factors for severe outcomes. The initial wave displayed the highest CFR (OR 5.28) especially in children aged 0-2 years. Conclusions: Children were less affected during the pandemic compared to adults; however, children under two years-old experienced more severe outcomes. Currently, with 95% of the population estimated to be immune due to vaccination and/or prior infection, children under 2 years of age are now at higher risk of severe disease and should be evaluated for vaccination as a public health policy.